CLASSIFICATION OF EXPRESSIVE MEANS AND STYLISTIC DEVICES - Axmedov , Namoz Boxodirovich (Educational Research in Universal Sciences, 2023)
The relationship between expressive means and stylistic devices is one of both similarity and distinction. Although they share commonalities, they do not possess identical meanings. While all stylistic devices fall within the realm of expressive means, not every expressive means can be categorized as a stylistic device. This distinction becomes evident in the context of phonetic elements, such as vocal pitch, pauses, logical stress, and distinct enunciation styles like drawling or staccato pronunciation. These phonetic phenomena serve as examples of expressive means, effectively conveying emotions and intentions, yet they do not necessarily qualify as stylistic devices within the framework of linguistic analysis.